Awareness on Resorbable Suture Material Among Dental Students - P, PATHMASHRI.V.; GANAPATHY, DHANRAJ; PANDURANGAN, KIRAN KUMAR; VELAYUDHAN, ASHOK (The journal of contemporary issues in business and government, 2020)
The aim of this study is to determine the understanding regarding resorbable suture material and its role in dentistry among dental students. To create awareness and determine the understanding of resorbable suture material and its role in dentistry among dental students. This study was conducted based on a questionnaire which consisted of 10 questions through a web-linked application called Survey Monkey. A convenient sample size of 100 consecutive dental students who are currently practicing in Chennai participated in the study. As an overall result, most of the participants are aware of resorbable suture material and their role in dentistry. As a conclusion, the awareness on resorbable suture material also its role and development among dental students in Chennai is adequate but certain knowledge has to be brushed up among them for a higher level. Furthermore, they need to be trained on these grounds to help them treat their patients with more consent and awareness.